People their needs - our responsibility [soundrecording] - Conant, Ralph (Development digest premier series, 1974)
Defines probable needs of the US population in the near future in terms of political philosophies and importance of information and education. Urges higher priorities for education and libraries among others. Outlines libraries' responsibilities in servicing the library's information needs. Challenges librarians to become active collectively in local and national politics to further their desired needs. Highlights the responsibilities of libraries in reducing ignorance and illiteracy around the world. Points out that the establishment of libraries historically proceeds the development of readers. Outlines current and future needs for boos, particularly in developing countries.